2014
DOI: 10.1007/s40596-014-0208-6
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Barriers and Facilitators for an Academic Career in Geriatrics: Medical Students’ Perspectives

Abstract: Objective There is a growing concern about a shortage of physician scientists. This problem is particularly severe in certain subspecialties such as geriatrics in general and geriatric psychiatry in particular. This study sought to obtain medical students’ perspectives on barriers and facilitators toward pursuing a career in academics and/or in geriatric psychiatry or medicine. Methods The study surveyed 27 first-year medical students from six US medical schools, who had demonstrated a clear interest in acad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(36 citation statements)
references
References 21 publications
0
32
0
Order By: Relevance
“…These represented clinical skills and attributes of the students rather than objective knowledge and suggest that students may feel a personal deficit in their ability to work with older people that influences preferences. In medical students, one qualitative study found that a lack of knowledge about academic careers and experience with older people was the most cited barrier to pursuing geriatrics or an academic geriatric career [53].…”
Section: Knowledgementioning
confidence: 99%
See 2 more Smart Citations
“…These represented clinical skills and attributes of the students rather than objective knowledge and suggest that students may feel a personal deficit in their ability to work with older people that influences preferences. In medical students, one qualitative study found that a lack of knowledge about academic careers and experience with older people was the most cited barrier to pursuing geriatrics or an academic geriatric career [53].…”
Section: Knowledgementioning
confidence: 99%
“…In general, positive and negative experiences with older people, regardless of setting, were considered influential and regarded as a central theme for nursing [39,58,64,65] and medical students [48,53].…”
Section: Experiences Of Students General Experiencesmentioning
confidence: 99%
See 1 more Smart Citation
“…[3][4][5][6][7][8][9][10][11][12][13] The Kidney TREKS Program was designed on the basis of these concepts ( Figure 1). Annually, 25 medical students and five graduate students are selected from a pool of applicants to join the cohort.…”
Section: Kidney Treks Program Designmentioning
confidence: 99%
“…Older persons will be the majority of patients they have to take care of, as age is the most significant risk factor of functional decline, disease, and disability[2]. This demographic change presents a plethora of challenges; the increasing demand for professional and informal caregivers being one of them[3]. Although ageing is a consequential part of life, older persons are often viewed in a negative light[4–6].…”
Section: Introductionmentioning
confidence: 99%